Study the Optical Properties of GQDs/AgNPs Nanosensor for Paraquat Detection - Janrungroatsakul, Wanwisa; Kaewnak, Wipawan; Insombat, Chanunporn (Burapha Science Journal, 2026)
In this work, GQDs/AgNPs nanosensor was prepared by reducing silver nitrate with sodium borohydride in the presence of graphene quantum dots (GQDs) solution. Optical properties of the prepared GQDs/AgNPs were studied by using UV-Vis spectroscopy and the GQDs/AgNPs were yellow in color due to strong surface plasmon resonance absorption band at 393 nm. The resulting decrease in absorption at 393 nm depended directly on increasing concentration of paraquat concomitant in the change of color of GQDs/AgNPs dispersion from yellow to orange. The linear concentration range of paraquat was 1 – 30 ppm with limit of detection of 0.4 ppm.